Chondroitin Sulfate Proteoglycan 4 and Its Potential As an Antibody Immunotherapy Target across Different Tumor Types - Ilieva, Kristina M.; Cheung, Anthony; Mele, Silvia; Chiaruttini, Giulia; Crescioli, Silvia; Griffin, Merope; Nakamura, Mano; Spicer, James F.; Tsoka, Sophia; Lacy, Katie E.; Tutt, Andrew N. J.; Karagiannis, Sophia N. (Frontiers in Immunology, 2018)
Overexpression of the chondroitin sulfate proteoglycan 4 (CSPG4) has been associated with the pathology of multiple types of such as melanoma, breast cancer, squamous cell carcinoma, mesothelioma, neuroblastoma, adult and pediatric sarcomas, and some hematological cancers. CSPG4 has been reported to exhibit a role in the growth and survival as well as in the spreading and metastasis of tumor cells. CSPG4 is overexpressed in several malignant diseases, while it is thought to have restricted and low expression in normal tissues. Thus, CSPG4 has become the target of numerous anticancer treatment approaches, including monoclonal antibody-based therapies. This study reviews key potential anti-CSPG4 antibody and immune-based therapies and examines their direct antiproliferative/metastatic and immune activating mechanisms of action.